2017
DOI: 10.1103/physrevb.95.054504
|View full text |Cite
|
Sign up to set email alerts
|

Coherent transport properties of a three-terminal hybrid superconducting interferometer

Abstract: Coherent transport properties of a three-terminal hybrid superconducting interferometerVischi, F.; Carrega, M.; Strambini, E.; D'Ambrosio, S.; Bergeret, F. S.; Nazarov, Yuli; Giazotto, F. Important noteTo cite this publication, please use the final published version (if applicable). Please check the document version above. CopyrightOther than for strictly personal use, it is not permitted to download, forward or distribute the text or part of it, without the consent of the author(s) and/or copyright holder(s)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…On the experimental side, topological properties of multi-terminal structures have been investigated in Refs. [15,16]. Elsewhere, it has been reported that complex spectra of Andreev reflections could originate from non-local entanglement of two or more Cooper pairs in three or more leads [17][18][19][20].…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the experimental side, topological properties of multi-terminal structures have been investigated in Refs. [15,16]. Elsewhere, it has been reported that complex spectra of Andreev reflections could originate from non-local entanglement of two or more Cooper pairs in three or more leads [17][18][19][20].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Finally the effects of the dissipative current on the magnitude of the supercurrent can be accounted for by self-heating in the device. Our experiment opens the prospects for future search of topological effects in multi-terminal graphene devices [11][12][13][14][15][16].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…(10) and (11), we see that, in principle, I (ϕ,h, P) = −I (−ϕ,h, P) and the zero-phase-difference current at ϕ = 0 is not prohibited by symmetry. From this simple analysis it is clear that the general features of the CPR can be deduced from the symmetry relations (10) and (11). First, we consider the S/FI/F/FI/S structure of Fig.…”
Section: Spin-filtering Boundary Conditions Beyond the Quasiclasmentioning
confidence: 99%
“…In certain cases, however, I c < 0, and the ground state corresponds to ϕ = π . Such π junctions can be realized, for example, in superconductor/ferromagnet/superconductor (S/F/S) structures [3][4][5][6], Josephson junctions with nonequilibrium normal metal interlayer [7], d-wave superconductors [8], semiconductor nanowires [9], gated carbon nanotubes [10], and multiterminal Josephson systems [11]. The π junctions have been suggested for building scalable superconducting digital and quantum logic [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1. In essence the proposed device realizes a Topological variant of the Superconducting Quantum Interference Proximity Transistor [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] or TSQUIPT. We characterize the TSQUIPT and its performance, and present calculations of the expected device behavior in transport experiments.…”
Section: Introductionmentioning
confidence: 99%